Exploring the effect of financial technology on the sustainability of small and medium enterprises in Mogadishu, Somalia - Mohamed Abdi Elmi; Faadumo Osman Abdulkadir; Akram Mahad Mohamud; Najmo Hussein Osman; Iqra Ali Abdi (Cogent Business & Management)
This study aims to explore the effect of financial technology (FinTech) on the sustainability of SMEs in Mogadishu, Somalia. It studies the impact of FinTech on the financial inclusion and literacy of SMEs and their mediating roles in the relationship between FinTech and SME sustainability. The research also analyzes the effect of financial inclusion and literacy on the sustainability of SMEs. This research adopted a cross-sectional survey methodology. The target population was entrepreneurs, SME owners, managers, and employees operating in Mogadishu. A purposive sampling method was used, and a sample of 385 participants was chosen. Then, questionnaires were utilized to gather primary data. The structural equation modeling technique, specifically partial least squares (SEM-PLS), was applied to examine the hypothesized relationships among the constructs. This study confirmed all seven conceptual hypotheses. This study found that FinTech significantly positively affects SME sustainability in Mogadishu. FinTech also increased SMEs’ financial inclusion and literacy, strengthening their sustainability. Financial inclusion and literacy have significant, positive, and complementary roles as partial mediators in the relationship between FinTech and SME sustainability. SMEs in Mogadishu need to embrace FinTech solutions to overcome existing obstacles to financial access and improve their financial health, further contributing to business sustainability.